Peningkatan Keterampilan Membaca melalui Model Pembelajaran Deep Learning di Sekolah Dasar Negeri 101103 Tolang Jae - Hasibuan, Nikmah Sari; Tambunan, Muhammad Syarif; Purba, Happy Sri Rezeki; Hasibuan, Emdra Syapudra; Pohan, Ade Rahmi Dani; Youmita, Hotna; Harahap, Fatma Suryani (Jurnal Bahastra, 2025)
This study aims to improve the reading skills of fourth-grade students at Public Elementary School 101103 Tolang Jae through the application of the deep learning instructional model. In this context, deep learning is not related to artificial intelligence algorithms but is employed as a pedagogical approach that emphasizes deep comprehension, reflection, and the application of concepts in real-life situations. The research employed a Classroom Action Research (CAR) design adapted from Kemmis and McTaggart’s model, which consists of four stages: planning, implementation, observation, and reflection. The study involved 28 students with varying literacy levels. Data were collected through reading literacy tests administered at each learning cycle and analyzed using quantitative descriptive methods. The results revealed a significant improvement in students’ literacy performance from cycle I to cycle II, indicated by an increase in the proportion of students scoring above 80, from 17.8% to 35.7%. The use of critical discussions, concept mapping, and meaning exploration effectively enhanced students’ understanding of reading materials and fostered critical thinking toward texts. Therefore, the deep learning-based instructional approach proved effective in improving reading literacy skills among elementary students, particularly in rural schools with limited learning resources.